Spatio-temporal variation of predatory hoverflies (Diptera: Syrphidae) and their relationship with aphids in organic horticultural crops in La Plata, Buenos Aires - Díaz Lucas, María Florencia (2020)
Population variations of predatory hoverflies in agroecosystems depend mainly on the resources that crops and wild vegetation provides them as well as death caused by natural enemies. We identified I) aphidophagous hoverfly species in lettuce and broccoli crops in Buenos Aires, II) the seasonal variations of the immature stages and their larval parasitism, and III) the wild plants, surrounding the crops, visited by adults. Fortnightly, 30 leaves were randomly selected in both crops during 2018-2019 and immature stages of syrphids and aphids per leaf were recorded. Adults were manually collected in patches of the wild plants (during 10 min of direct observations), and plants visited by adults were determined. The hoverflies were Allograpta exotica Wiedemann and Toxomerus duplicatus Wiedemann. Only A. exotica was recorded in crops. The dominant aphids were Myzus persicae (Sulzer) in lettuce and Brevycorine brassicae (L.) in broccoli. Parasitism rates ranged between 8 and 100% and the species were Diplazon laetatorius (Fabricius), in both crops, and Pachyneuron aff. nelsoni only in broccoli. Galinsoga parviflora Cav. and Matricaria chamomilla L. were the wild plants most often visited by hoverflies. This work provides basic information for the control of aphids by hoverflies in the framework of conservation biological control.